PENGARUH KUALITAS PELAYANAN, ATRIBUT PRODUK ISLAM, DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH - Rahayu Triastity, Suranto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
Purpose of this research to analyze the effect of service quality, Islamic product attributes and customer value on customer satisfaction and analyze the factors that dominant effect on customer satisfaction. This study is a survey on customer KJKS Bina Insan Mandiri. This type of data is qualitative data and quantitative data. Source of data used primary data and secondary data. Sample research are 100 customers with accidental sampling technique. The technique of collected data use questionnaires, observation and documentation. Analysis of data use multiple linear regression. The results showed that the service quality has positive and significance effect on customer satisfaction. Islamic product attributes has positive and significant positive effect on customer satisfaction. Customer value has positive and significant effect on customer satisfaction. Islamic product attributes is the dominant variable who effect on customer satisfaction. The magnitude of the effect of service quality, Islamic product attributes and customer value by 53,2 percent. Keywords: service qeuality, Islamic product attributes, customer value and customer satisfaction.